Use of flash card media to improve english vocabulary memory for class V students at SDN 205/IV Jambi - Kurniati, Erisa; Fitri, Nurul; Jufrizal, Jufrizal; Fauzan, Ahmad (Electronic Journal of Education, Social Economics and Technology, 2023)
This study aims to describe the use of flashcard media in learning English vocabulary in 5th-grade elementary school students and improve the memory of 5th-grade elementary school students through the use of flashcard media. This study used the theory of Djunaidi Fauzan (2012). This study uses a descriptive qualitative method. This research explains facts and characteristics factually and carefully, which will later be drawn to conclusions. The participants in this study consisted of 4 people: three students and an English teacher. This study collected data using observation, interview, and test techniques. The results showed that learning using flashcard media improved students' memory in learning English for class V at SDN 2015/IV Jambi. The increase in students' vocabulary can be seen from the observation results, which increased by several points, and the test results, which increased by 15%. Apart from observations and tests, the results of interviews also show that the use of flash card media can attract students' attention so that their memory of the new vocabulary also acquired increases.